Determination of aflatoxin B1 by novel nanofiber-packed solid-phase extraction coupled with a high performance liquid chromatography-fluorescence detector. Issue 4 (5th January 2023) - Wang, Yunzheng; Hou, Chen; Dai, Yuqi; Chu, Lanling; Geng, Shiwei; Zheng, Shenglan; Kang, Xuejun
Abstract : A novel analytical proposal based on nanofiber-packed solid-phase extraction coupled with high performance liquid chromatography-fluorescence detector (HPLC-FLD) has been successfully developed for determining aflatoxin B1 (AFB1) in foods. Abstract : A novel analytical proposal based on nanofiber-packed solid-phase extraction coupled with high performance liquid chromatography-fluorescence detector (HPLC-FLD) has been successfully developed for determining aflatoxin B1 (AFB1) in foods. Four types of nanofibers, including polystyrene (PS) nanofibers, polypyrrole (PPY) nanofibers, polystyrene–acrylic resin (PS–AR) nanofibers, and polystyrene–polyvinyl pyrrolidone (PS–PVP) nanofibers, were fabricated by electrospinning and utilized to prepare a home-made extraction device. In this study, the factors of different fibers, namely, fiber dosage, pH of extraction solution, type of salt ion, concentration of salt ion, and volume of the eluent were optimized. Under optimized conditions, the method showed good linearity in the range of 0.1–40 ng mL −1 with a correlation coefficient greater than 0.999 and good inter-day accuracy (90.8–112.7% recovery) and precision (1.8–3.6% intra-day RSDs, 2.6% inter-day RSD), and the limit of detection (LOD) was 0.05 ng mL −1 . Due to its cost-effective, time-saving, environmentally friendly, and simple performance, it has the potential to be utilized to determine aflatoxins in complicated matrices.